2016
DOI: 10.1001/jamaophthalmol.2016.1678
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Industry Interactions and Anti–Vascular Endothelial Growth Factor Use Among US Ophthalmologists

Abstract: The publication of the US Physician Payments Sunshine Act provides insight into the financial relationship between physicians and the pharmaceutical industry. This added transparency creates new opportunities of using objective data to better understand prior research that implicates pharmaceutical promotions as an important factor in a physician's decision-making process.OBJECTIVE To assess the association between reported industry payments and physician-prescribing habits by comparing the use of anti-vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 28 publications
2
75
1
Order By: Relevance
“…This may explain why the current study produced disparate results for median prescription counts but detected some effect in outlier analyses (ie, enzalutamide regression and quantile analysis). This is consistent with another study that similarly performed correlation analyses on antivascular endothelial growth factor drugs in patients with neovascular eye disease . Together, all 3 studies suggest that there is an association among outliers; however, it is less clear whether token dollar values centered on median values significantly influence prescriber behavior .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This may explain why the current study produced disparate results for median prescription counts but detected some effect in outlier analyses (ie, enzalutamide regression and quantile analysis). This is consistent with another study that similarly performed correlation analyses on antivascular endothelial growth factor drugs in patients with neovascular eye disease . Together, all 3 studies suggest that there is an association among outliers; however, it is less clear whether token dollar values centered on median values significantly influence prescriber behavior .…”
Section: Discussionsupporting
confidence: 85%
“…The results of the current study demonstrate that there was no difference in prescription counts between Open Payments recipients and nonrecipients. This is in contrast to recent analyses that have suggested a positive relationship between payments and prescription patterns using similar databases . One study evaluated the ratio of prescriptions comparing brand‐name drugs versus generics in statins, beta blockers, angiotensin‐converting enzyme inhibitors, and angiotensin receptor blockers .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Increased contact with and payment from industries may lead to increased physician loyalty to particular brands of new technologies and manifest itself as increased utilization of industry products. Several studies have demonstrated that increasing usage of new medications and technologies is associated with increasing industry payments across medical subspecialties . Particularly for new technologies such as BD, close contact with industry representatives may be required to better understand and apply the technology.…”
Section: Introductionmentioning
confidence: 99%